Recepcja pism Niccolò Machiavellego w "Rozmowie Plebana z Ziemianinem" Łukasza Opalińskiego - Maciejewska, Anna (Melusine. Old Literature and Culture, 2026)
The purpose of this article is to show the impact of Niccolò Machiavelli’s idea on Łukasz Opaliński’s “A Parish Priest’s Conversation With a Landowner”. The author of article noticed that for both of these political writers, virtue, good laws and customs were very important. First of all, however, the article presented examples of references by the Polish poet and writer of the baroque to such works as “The Prince” and “Discourses on the First Decade of Titus Livius”. The author also pointed out what influence this reception of Niccolò Machiavelli’s writings.